Pre versus post application of a 0.12% chlorhexidine based oral hygiene protocol in an Egyptian pediatric intensive care unit: Practice and effects - Mohamed Mustafa Gomaa; Yahya Wahba; Mohammed Attia El-Bayoumi (Egyptian Journal of Critical Care Medicine, 2017)
Background: The role of oral hygiene in the intensive care unit is indisputable. Several studies were carried out in different pediatric intensive care units using different oral hygiene regimes. Chlorhexidine preparations are widely used in oral care regimes. Aim: This study was conducted in the pediatric intensive care unit of Children’s Hospital of Mansoura University, Egypt to unravel the effect of adoption of an oral hygiene protocol using 0.12% chlorhexidine solution on the outcome of mechanically ventilated patients. Methods: The study comprised 50 patients admitted in the period from January 2013 to August 2016. The sample was analyzed as follow: intervention group (28 patients) and control group (22 patients). The intervention group received a 0.12% chlorhexidine based oral hygiene protocol while the control group received usual oral care without chlorhexidine. Mann-Whitney and Chi-square tests were used. Results: Duration of mechanical ventilation and length of stay were significantly reduced in the intervention group (p =.003 and .007 respectively). Statistically insignificant difference in development of ventilation-associated pneumonia and mortality between both groups was shown (p = .068 and .208 respectively). Conclusions: Adoption of a 0.12% chlorhexidine based oral hygiene regime was associated with improved outcome in pediatric intensive care unit.